Γ-glutamylcysteine suppresses cadmium-induced apoptosis in PC12 cells via regulating oxidative stress. (15th January 2022) - Bi, Aijing; Guo, Zhen; Yang, Guocui; Huang, Youfang; Yin, Zhimin; Luo, Lan
Graphical abstract: A schematic representation of the proposed molecular mechanism of inhibiting effects of γ-GC against Cd-induced apoptosis in PC12 cells. Highlights: γ-GC suppresses Cd-induced apoptosis in PC12 cells. γ-GC alleviates Cd-induced oxidative stress in PC12 cells. γ-GC represses Cd-induced MAPK and PI3K/Akt pathways by inhibiting oxidative stress. γ-GC ameliorates Cd-induced neurotoxicity by repressing MAPK and PI3K/Akt pathways. Abstract: Cadmium (Cd) is a highly toxic environmental pollutant, leading to the occurrence and development of multiple neurological diseases. γ-glutamylcysteine (γ-GC) is a dipeptide formed by the condensation of l -glutamic acid and l -cysteine, which has antioxidant, anti-inflammatory, and chelating properties. The purpose of this study is to investigate the effect of γ-GC on Cd-induced apoptosis in PC12 cells. PC12 cells were pretreated with or without γ-GC (2 mM or 4 mM) for 2 h and exposed to Cd (10 μM) for 12 h, and survival, apoptosis, and oxidative stress of PC12 cells were detected after different treatments. The results showed that γ-GC significantly inhibited cell viability reduction, apoptosis, and depolarization of mitochondrial transmembrane potential in Cd-treated PC12 cells, as indicated by CCK-8 assay, flow cytometry, TUNEL staining, and JC-1 detection. Western blot showed that γ-GC down-regulated the ratio of Bax/Bcl-2 and the protein levels of cytosolic cytopigment c, cleaved-caspase-9, cleaved-caspase-3, and cleaved-PARP. Mechanistically, γ-GC suppressed Cd-induced ROS production, MDA accumulation, and GSH depletion, and increased the activity of antioxidant enzymes. Cd-induced activation of MAPK and PI3K/Akt signaling pathways were inhibited by γ-GC treatment, while sustained phosphorylation of JNK, p38, or Akt reversed anti-apoptotic effects of γ-GC. These results suggested that γ-GC inhibited Cd-induced apoptosis in PC12 cells through decreasing oxidative stress and inhibiting the activation of MAPK and PI3K/Akt signaling pathways. γ-GC could be used as a potential protective agent against Cd neurotoxicity.